2009
DOI: 10.5380/ce.v14i3.16187
|View full text |Cite
|
Sign up to set email alerts
|

Vivência Da Amamentação Por Mães-Adolescentes

Abstract: RESUMO:A amamentação é um ato de grande importância e benefício para a mãe e o filho e não há contraindicação para mães-adolescentes. O objetivo desta pesquisa é descrever a vivência da amamentação na adolescência e observar a ocorrência de desmame precoce. Trata-se de estudo qualitativo de abordagem descritiva, utilizando a técnica de grupo focal, realizada em um Centro de Saúde de uma Região Administrativa do Distrito Federal no ano de 2008. Os resultados obtidos revelaram que não está ocorrendo o desmame pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…It is in this space that the nursing mothers seek shelter and support to organize the household chores and maternal care, support that often comes from the same genre: mothers, mothers-in-law, sisters, sisters-in-law and friends. 5,8,10 The speeches infer that breastfeeding beyond the condition of an individual technique, because their practice is determined by the insertion of women in their social and organizational relationships that are built in different institutions and societies. 9 These results corroborate with a study that showed the prevalence of breastfeeding being influenced by differences of race, family income, and population density of the area of residence, mother's age, level of education, and your current marital status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in this space that the nursing mothers seek shelter and support to organize the household chores and maternal care, support that often comes from the same genre: mothers, mothers-in-law, sisters, sisters-in-law and friends. 5,8,10 The speeches infer that breastfeeding beyond the condition of an individual technique, because their practice is determined by the insertion of women in their social and organizational relationships that are built in different institutions and societies. 9 These results corroborate with a study that showed the prevalence of breastfeeding being influenced by differences of race, family income, and population density of the area of residence, mother's age, level of education, and your current marital status.…”
Section: Resultsmentioning
confidence: 99%
“…In the negative perspective the disinterest, lack of encouragement to the act of breastfeeding and the lactating pressure in shown on the form of nutrition for their child. 10 During the teenager's breastfeeding process, the opinions of her companion and mother are crucial for the continuity of exclusive breastfeeding decision or the insertion of novel foods in the diet of their child. 11 Given this, health professionals have as their main function the priority tracking teenage nursing mothers, with a view to meeting their beliefs and family history, with the objective of increasing the prevalence of breastfeeding among these young mothers.…”
mentioning
confidence: 99%
“…A literatura recomenda que até os seis meses de vida, o leite materno deve ser a única fonte de alimentos da criança, pois possui capacidade oferecer aporte proteicocalórico adequado, favorecendo sua proteção contra doenças e o seu desenvolvimento (19)(20) . Um estudo mostrou que a prevalência de aleitamento exclusivo tem sido menor entre adolescentes, e o desmame completo no final do terceiro mês também tem sido maior entre esse grupo (21) . Outro estudo evidenciou que o desmame geralmente acontece dentro das primeiras semanas após o nascimento, o período crítico, em que muitas mães acham seu leite insuficiente, tomam medicações ou experienciam traumas mamilares ou dor mamária (19) .…”
Section: Discussionunclassified